Human Albumin Use in Adults in U.S. Academic Medical Centers. Issue 1 (January 2017) - Suarez, Jose I.; Martin, Renee H.; Hohmann, Samuel F.; Calvillo, Eusebia; Bershad, Eric M.; Venkatasubba Rao, Chethan P.; Georgiadis, Alexandros; Flower, Oliver; Zygun, David; Finfer, Simon
Abstract : Objective: To determine rates and predictors of albumin administration, and estimated costs in hospitalized adults in the United States. Design: Cohort study of adult patients from the University HealthSystem Consortium database from 2009 to 2013. Setting: One hundred twenty academic medical centers and 299 affiliated hospitals. Patients: A total of 12, 366, 264 hospitalization records. Interventions: Analysis of rates and predictors of albumin administration, and estimated costs. Measurements and Main Results: Overall the proportion of admissions during which albumin was administered increased from 6.2% in 2009 to 7.5% in 2013; absolute difference 1.3% (95% CI, 1.30–1.40%; p < 0.0001). The increase was greater in surgical patients from 11.7% in 2009 to 15.1% in 2013; absolute difference 3.4% (95% CI, 3.26–3.46%; p < 0.0001). Albumin use varied geographically being lowest with no increase in hospitals in the North Eastern United States (4.9% in 2009 and 5.3% in 2013) and was more common in bigger (> 750 beds; 5.2% in 2009 and 7.3% in 2013) compared to smaller hospitals (< 250 beds; 4.4% in 2009 to 6.2% in 2013). Factors independently associated with albumin use were appropriate indication for albumin use (odds ratio, 65.220; 95% CI, 62.459–68.103); surgical admission (odds ratio, 7.942; 95% CI, 7.889–7.995); and high severity of illness (odds ratio, 8.933; 95% CI, 8.825–9.042). Total estimated albumin cost significantly increased from 325 million in 2009 to 468 million in 2013; (absolute increase of 233 million), p value less than 0.0001. Conclusions: The proportion of hospitalized adults in the United States receiving albumin has increased, with marked, and currently unexplained, geographic variability and variability by hospital size. Abstract : Supplemental Digital Content is available in the text.